The Effects of Group Psychoeducational Programme on Attitude toward Mental Illness in Families of Patients with Schizophrenia, 2014 - Rahmani, Farnaz (J Caring Sci, 2015)
Introduction: Family members often play a vital role as caregivers in the lives of individuals with schizophrenia. Results of the studies showed that family invironment is the most important determinint of patients outcomes like as quality of life, relapse, adherence. This study aimed to determine the effect of group psychoeducational programme on attitude towards mental illness in families of patients with schizophrenia. Methods: In this quasi-experimental study, 74 families who have schizophrenic patients hospitalized in psychiatric wards during sampling were selected by convenience sampling method. Then the sample was randomly assigned to experimental and control groups. The families of experimental group received 8 continuous 90-minute 3 times a week psychoeducational sessions. Family attitude towards mental illness was measured using the questionnaire of Opinion about Mental Illnesses (OMI) before and after intervention. Data analysis was conducted using χ(2) test, independent t-test, and paired t-test on SPSS software version 13. Results: The results showed that majority of the families had negative attitude towards mental illness (88.90%). In addition, the results showed that there was significant difference between different dimensions of attitude towards mental illness before and after psychoeducation in the experimental group. The mean score of families' post-test in the experimental group increased compared to control group 108.86 (14.9), vs. 88.86 (7.5). Conclusion: The results of this study indicate that psychoeducation improves family attitude towards mental illness. Training methods like group psych education for the families of mental patients can be effective on their attitudes towards mental illness.